Application of SWOT Analysis in Determining Marketing Strategy at PT. Aquafarm Nusantara Naga Kisar Perbaungan - Ella Silvana Ginting; Dinda aisyah; M. Umar Maya Putra (Jurnal Mantik, 2020)
This study aims to analyze the strengths, weaknesses, threats, and opportunities that exist in PT. Aquafarm Nusantara Naga Kisar Perbaungan. This research is a type of qualitative research method that uses a quantitative approach. The qualitative method uses IFAS (Internal Factor Analysis Strategy) and EFAS (External Factor Analysis Strategy) matrices which are then processed by AHP (Analytical Hierarchy Process) to assist data processing and make decisions in implementing strategies at PT. Aquafarm Nuantara Naga Kisar Perbaungan. The results of this study indicate that PT. Aquafarm Nusantara Naga Kisar Perbaungan in the SWOT diagram is in quadrant 3, then the right strategy for the company to run is to support the turn around strategy by implementing the WO (weaknesses opportunities) strategy. where the strategy can be healthy for the company. From the results of the AHP (Analytical Hierarchy Process) processing, it was obtained a proposal to run method 2 (new), namely by lowering product prices by making adjustments to current economic conditions and increasing the quality of human resources. PT. Aquafarm Nusantara Naga Kisar Perbaungan is expected to reshape the structure of the marketing division and innovate products in accordance with current market conditions.